1979
DOI: 10.1038/bjc.1979.50
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumour activity of ICI 118630, a new potent luteinizing hormone-releasing hormone agonist

Abstract: Summary.-Experiments were undertaken with DMBA -induced mammary tumours of the rat to determine the anti-tumour properties of a new and potent luteinizing hormone-releasing hormone (LH-RH) agonist, [D-Ser(But) 6AzglylO]-LH-RH (ICI 118630). Tumours were classified according to their oestrogen-receptor (ER) content. Twice daily i.m. injections of either 5 ,ug or 0-5 ,ug ICI 118630 in saline were as effective as ovariectomy or tamoxifen therapy in causing the regression of ER+ DMBA-induced mammary tumours. ER-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1981
1981
1992
1992

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…DMBA-induced mammary tumors will regress after removal of the ovaries or the pituitary gland and in response to treatment with antiestrogenic agents (4)(5)(6). Several studies have shown that chronic administration of agonistic analogs of luteinizing hormone-releasing hormone (LH-RH) can inhibit the growth of mammary tumors induced by DMBA in rats (7)(8)(9)(10). This tumor-suppressing action of LH-RH agonists can be nullified by administration of estradiol.…”
mentioning
confidence: 99%
“…DMBA-induced mammary tumors will regress after removal of the ovaries or the pituitary gland and in response to treatment with antiestrogenic agents (4)(5)(6). Several studies have shown that chronic administration of agonistic analogs of luteinizing hormone-releasing hormone (LH-RH) can inhibit the growth of mammary tumors induced by DMBA in rats (7)(8)(9)(10). This tumor-suppressing action of LH-RH agonists can be nullified by administration of estradiol.…”
mentioning
confidence: 99%
“…Although an acute injection of superactive analogues of LH-RH causes a marked and prolonged release of gonadotropins, paradoxically, chronic administration results in chemical castration as evidenced by decreased estrogen levels and atrophy of the ovaries and uterus in female rats and by a decrease in plasma testosterone and weights of testes and accessory sex organs in male rats (7,8). These paradoxical inhibitory effects, induced by chronic administration of superactive analogues of LH-RH, have been linked with the regression of the growth of 7,12-dimethylbenzen[a]anthracene-induced mammary carcinomas in the rat (9)(10)(11)(12). In one study, an LH-RH analogue proved to be as effective as ovariectomy or tamoxifen treatment in causing regression of these tumors which were estrogen-receptor positive (11).…”
mentioning
confidence: 99%
“…They suggested that tamoxifen acts by blocking estrogen receptors of the tumor, whereas the LH-RH agonist induces a chemical castration. These studies (9)(10)(11)(12)(13) (17). One hundred forty days after transplantation, the tumors were palpable, and rats bearing tumors 25 mm3 or greater were selected for study.…”
mentioning
confidence: 99%
“…Results of this approach, however, are still controversial both in terms of response rates and with regard to whether it is a reliable tool for predicting the effectiveness of subsequent ovarian ablation therapy [30,32,54], Soon after the introduction of agonist of the luteinizing hor mone-releasing hormone (LH-RH) designed for the treatment of primary sterility or endometriosis, it became apparent that these substances induced a dow'n-regulation of pituitary recep tors thus leading to a sustained hypogonadotropic ovarian insufficiency. Subsequent preclinical studies showed that LH-RH agonists were effective in a variety of hormone dependent tumors, including DMBA-induced mammary tumors in female rats [50,57], During the last five years, analogues of LH-RH have been investigated in pre-and postmenopausal women. Encouraging results have been obtained in premenopausal patients with metastatic breast cancer [22,23,38-42, 65, 66].…”
Section: A G O N Ists O F the L U Teotropic H O Rm O N E R Eleasing Hmentioning
confidence: 99%